A Phenomenological Discussion about Floral Symbolisms, Olfaction & Music themes in Lived Experiences - Martin, Bradley Jerad (Stellenbosch : Stellenbosch University, 2025)
Thesis (MMus)--Stellenbosch University, 2025.